How should developing countries adjust to external shocks in the 1980s? : an examination of some World Bank macroeconomic models - Sanderson, Warren C.; Williamson, Jeffrey G. (Washington, D.C., U.S.A. : World Bank, 1985)
This paper arose out of the desire to review the quantitative relationship between external shocks, economic policies and performance across a sample of developing countries, as background to the World Development Report 1984.
Bibliography: p. 97-98.
osa; 23/08/18
Loans
Keywords: Economic stabilization; Economic policy - mathematical model; Developing countries